Construction and pilot assessment of the Upper Limb Assessment in Daily Living Scale. Issue 6 (6th March 2012) - Rousseaux, Marc; Bonnin-Koang, Huei-Yune; Darné, Bernadette; Marque, Phillippe; Parratte, Bernard; Schnitzler, Alexis; Dehail, Patrick; Bradai, Nacera; Viton, Jean Michael; Daveluy, Walter; Yelnik, Alain; Zadikian, Myriam; et al.
Abstract : Objective: The upper limb function of hemiplegic patients is currently evaluated using scales that assess physical capacity or daily activities under test conditions. The present scale, the Upper Limb Assessment in Daily Living (ULADL) Scale, was developed to explore the subjective and objective functional capacities of such patients in a proximal to distal sequence. Methods: A group of experts constructed a scale addressing 17 upper limb functions (five active passive and 12 active) which could be explored by a questionnaire (Q) and a test (T). Reproducibility, internal consistency, concurrent validity (Rivermead Motor Assessment (RMA)) and learning effect were estimated in a multicentre study. Results: 49 stroke patients were each rated three times within 7 days by a total of 21 physicians, yielding a total of 142 ratings. The ULADL took 16±8 min to complete compared with 9±5 min for the RMA. Cronbach's alpha coefficient was 0.95 for Q and 0.97 for the practical tests (T). The global Q and T scores, and in particular the global Q score, were slightly higher at the second rating. The intra-rater intraclass correlation coefficient (ICC) was 0.65 (95% CI (0.44 to 0.79)) for Q and 0.97 (0.95 to 0.98) for T, and the inter-rater ICC was 0.95 for both Q and T. The Bland and Altman method showed good intra- and inter-rater reliability with no systematic trend. Correlation coefficients for ULADL versus RMA were >0.80 for both Q and T. Conclusions: The ULADL Scale has good psychometric properties and can explore patients with different degrees of upper limb impairment.